2018
DOI: 10.3390/nu11010018
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Zinc and Risk of Prostate Cancer in Spain: MCC-Spain Study

Abstract: Zinc is a key trace element in normal prostate cell metabolism, and is decreased in neoplastic cells. However, the association between dietary zinc and prostate cancer (PC) in epidemiologic studies is a conflicting one. Our aim was to explore this association in an MCC-Spain case-control study, considering tumor aggressiveness and extension, as well as genetic susceptibility to PC. 733 incident cases and 1228 population-based controls were included for this study. Dietary zinc was assessed using a food frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…However, a recent evaluation of the relationship between dietary zinc intake and the disease grade and stage by Gutiérrez-González et al [27] did not support this association. Additionally, Park et al [28] found no association between serum zinc status and PCa grade and stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent evaluation of the relationship between dietary zinc intake and the disease grade and stage by Gutiérrez-González et al [27] did not support this association. Additionally, Park et al [28] found no association between serum zinc status and PCa grade and stage.…”
Section: Discussionmentioning
confidence: 99%
“…Also, epidemiologic studies on Zn actions and risk of PCa are ambiguous and provide conflicting results. Recently, Gutierrez-Gonzalez et al (2019) [15] proved that high dietary zinc intake could be associated with a higher PCa risk (especially for low-grade and localized tumors) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Normal cells of peripheral zone accumulate high contents of Zn, in contrast to neoplastic, in which Zn concentration is remarkably lower, what results in reduced pro-apoptotic effects of this element. Therefore, it is hypothesized that increasing Zn concentrations can promote the apoptosis of malignant cells and inhibit neoplastic cell proliferation, migration, and invasion [15,16]. Similarly to Zn, Se is also used in anticancer supplementation, as it offers protection against free radicals, modifies immunity, DNA repair, apoptosis, and angiogenesis [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…However, when prostate cancer was diagnosed at the advanced stage, any significant effect of higher zinc intake was not observed. In turn, the results from the MCC-Spain case–control study [ 150 ] covering 733 men with prostate cancer and 1228 population-based control individuals revealed that the dietary zinc intake at the level of at least 10.53 mg/day vs. 8.34 mg/day or less was associated with a 39% higher risk of prostate cancer (OR = 1.39, 95% CI = 1.00–1.95). When zinc intake was compared with prostate cancer aggressiveness, it turned out that patients with a low-grade tumor (Gleason score = 6) more frequently consumed zinc at a higher level (relative risk ratio = 1.66, 95% CI = 1.07–2.57) than patients who consumed less than 8.34 mg/day.…”
Section: The Role Of Nutritional Factors and Foodstuffs On Prostatmentioning
confidence: 99%